Proceedings of the 17th Iron Age research student symposium, Edinburgh : 29th May - 1st June 2014 - Erskine, Graeme J. R.,; Jacobsson, Piotr,; Miller, Paul,; Stetkiewicz, Scott, (Access archaeology., 2016)
This work contains the proceedings of the 17th Iron Age Research Student Symposium held in Edinburgh, organised to reflect three general themes (migration/interaction, material culture and the built environment).